Penerapan Metode Analytical Hierarchy Process (AHP) dan Metode Simple Additive Weighting (SAW) pada Pembiayaan Anggota (Studi Kasus: Koperasi Simpan Pinjam Pembiayaan Syariah Tunas Artha Mandiri (KSPPS TAM) di Kab. Nganjuk) - Hinandy Nur Anisa; Edy Santoso; Lailil Muflikhah (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Tunas Artha Mandiri Sharia Financing Savings And Loan Cooperative (KSPPS TAM) is a Sharia financial institution in the form of a savings and loan cooperative located in Nganjuk Regency. In the past 3 years, the demand for member financing has increased, because it makes it difficult for cooperatives to determine whether members deserve financing assistance or not. The Simple Additive Weighting Method (SAW) and The Analytical Hierarchy Process (AHP) Method are two of the methods taken for this study. Things are obtained from both methods, namely the optimal level of accuracy and the accuracy of providing member financing. AHP method was chosen because a complex problem was converted into a hierarchy, while the SAW method was chosen because of the weighted addition to the performance rating. The study used 3 criteria, namely income, employment, and the ability to pay installments. Obtaining AHP accuracy with 5 data by 100% and 50 data by 90%. Meanwhile, the accuracy results obtained by the SAW method with 5 data by 80% and 50 data by 78%. The results of the accuracy assessment analysis obtained by the AHP method are more accurate than the SAW method.